Gellan gum-based nanocomposites films containing bio-reduced silver nanoparticles: Synthesis, characterisation and antifungal activity - Laura Di Muzio; Francesco Cairone; Stefania Cesa; Claudia Sergi; Jacopo Tirillò; Letizia Angiolella; Andrea Giammarino; Gustavo Giusiano; Stefania Petralito; Maria Antonietta Casadei; Patrizia Paolicelli (Carbohydrate Polymer Technologies and Applications, 2024)
The aim of this work was to develop and characterise nanocomposite thin films containing silver nanoparticles (AgNPs), as wound dressings and antifungal materials, using a green process for the nanoparticles’ synthesis and a single step procedure for the preparation of the nanocomposite films. To this end, polyphenol-rich extracts obtained from kiwi peels, an agri-food industrial by-product, were used as a reducing agent of silver nitrate salt. The AgNPs were let form within the film-forming solution, which was composed by low acyl gellan gum and a plasticising agent (glycerol or PEG 400 g/mol) and the corresponding nanocomposite films were deposited by the solvent casting technique. The plasticising agent affected the AgNPs distribution within the films, as observed by SEM and EDS analyses, and consequently their tensile behaviour. In specific, AgNPs act as stress intensifiers in the presence of glycerol, whereas they act as film reinforcement with PEG400. However, both glycerol-plasticised and PEG400-plasticised films exhibited similar antifungal efficacy against 16 clinical isolates of 5 different Candida spp (C. albicans, C. lusitaniae, C. haemulonii, C. krusei and C. glabrata). Globally, the present study provides a green and single-step procedure to develop nanocomposite films embedding AgNPs obtained by in situ reduction of silver ions with polyphenol-rich extracts.